Resonance Monitoring of a Horizontal Wind Turbine by Strain-Based Automated Operational Modal Analysis - Wei-Hua Hu; De-Hui Tang; Ming Wang; Jun-Le Liu; Zuo-Hua Li; Wei Lu; Jun Teng; Samir Said; Rolf. G. Rohrmann (Energies, 2020)
A strain-based automated operational modal analysis algorithm is proposed to track the long-term dynamic behavior of a horizontal wind turbine under operational conditions. This algorithm is firstly validated by a scaled wind turbine model, and then it is applied to the dynamic strain responses recorded from a 5 MW wind turbine system. We observed variations in the fundamental frequency and 1f, 3f excitation frequencies due to the mass imbalance of the blades and aerodynamic excitation by the tower dam or tower wake. Inspection of the Campbell diagram revealed that the adverse resonance phenomenon and Sommerfeld effect causing excessive vibrations of the wind tower.